Unusual and persistent easterlies restrained the 2023/24 El Niño development after a triple-dip La Niña - Ji-Won Kim; Baijun Tian; Jin-Yi Yu (npj Climate and Atmospheric Science)
Abstract The 2023/24 El Niño, emerging after a rare triple-dip La Niña, garnered global attention due to its potential to evolve into an extreme event, given the largest accumulation of warm water in the equatorial western Pacific since 1980. Despite initial expectations, its growth rate unexpectedly decelerated in mid-2023, preventing it from reaching the anticipated intensity. Here, we show through observational analyses that unusual easterly anomalies over the tropical western-central Pacific, persisting after the end of the preceding La Niña, significantly contributed to this slowdown. A prominent east‒west sea surface temperature gradient in the region has been identified as the crucial factor associated with these unusual and persistent easterly anomalies. This temperature gradient is directly attributed to a negative North Pacific Meridional Mode and a deepened thermocline over the Philippine Sea. These findings offer a deeper understanding of the atypical transition from a prolonged multi-year La Niña to an El Niño.